Analisis Finansial dan Manajemen Risiko Dalam Studi Kelayakan Bisnis Syifa Laundry - Vientiany, Dini; Harahap, Isnaini Nur; Prayoga, Muhammad Ilham; Hutasuhut, Syahnazwa Aiska Hidayat (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study is motivated by the increasing competition in the laundry service business in urban areas, along with changes in lifestyle that demand practicality and time efficiency. These conditions require business owners to implement sound financial management and effective risk management to ensure business sustainability, particularly in the case of Syifa Laundry. The purpose of this study is to analyze the business feasibility of Syifa Laundry from financial and risk management aspects. This research employs a descriptive qualitative method with a business feasibility study approach, supported by direct observation, interviews with the business owner, and literature review from relevant journals and books. The results indicate that Syifa Laundry generates relatively stable revenue with higher customer demand on specific days. From the financial aspect, the business is able to cover its operational costs and reach the break-even point within approximately eight months after commencing operations. From the risk management aspect, Syifa Laundry has implemented simple yet effective measures in handling operational and service-related risks. Based on these findings, Syifa Laundry is considered feasible to operate and has potential for future development. Future research is recommended to incorporate more in-depth quantitative financial analysis and expand the scope of the study to achieve more comprehensive results.